METODE PENDIDIKAN AKHLAK PERSPEKTIF HADIS: TELAAH KITAB ADAB ṢAḤĪḤ AL-BUKHĀRĪ - Samsuddin, Samsuddin; Kasman Bakry (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This study aims to determine the concepts and methods of moral education in the chapter on adab in the book of Ṣaḥīḥ al-Bukhārī. This research is literature research using a historical sociological approach and data processing is carried out using qualitative methods. The results showed that the study of adab and morals received great attention from the hadith of the Prophet. The methods of moral education used vary based on the concept of human nature which loves goodness. The results of this study are expected to contribute to the field of education, including management and management based on nabawi morals.